Análise genético-quantitativa da eficiência produtiva de um rebanho bovino da raça Canchim - Mello, Silvio de Paula (2004)
Genetic parameters for body weight at weaning (PD), at twelve months of age (P12), at first calving (PPP) and at adult age (PAD), condition score at calving (ECP) and at first calving (EPP), growth curve parameters A (asymptotic weight) and k (maturation rate), age at first calving (IPP), culling age (TPR, days in herd), number (ND10) and kilograms (QD10) of calves weaned up to ten years of age, total number (NDT) and total kilograms (QDT) of calves weaned during herd life, kilograms of calves weaned per year in herd (QTPR), and the ratios weaning weight of calf/weight of cow at calving (RPP) and weaning weight of calf/weight of cow at first calving (RPPP) of females of a Canchim (5/8 Charolais + 3/8 Zebu) beef cattle herd were estimated by Bayesian inference. The average values of heritability were 0.38 (PD), 0.40 (P12), 0.51 (PPP), 0.54 (PAD), 0.18 (ECP), 0.36 (EPP), 0.60 (A), 0.54 (k), 0.12 (IPP), 0.22 (TPR), 0.22 (ND10), 0.24 (QD10), 0.23 (NDT), 0.23 (QDT), 0.32 (QTPR), 0.16 (RPP) and 0.40 (RPPP), indicating that these traits have enough genetic variability to show response to mass selection, with the exception of IPP. The genetic correlations of TPR, ND10, QD10, NDT, QDT and QTPR with the body weights (PD, P12 and PD) suggest that selection of females based on weaning and 12-month body weights should not reduce the produtivity traits studied; however, increasing females adult body weight would reduce the number of calves weaned by the cow up to ten years of age. The genetic correlations of TPR, ND10, QD10, NDT, QDT, QTPR, PAD, A and k with IPP, PPP and EPP suggest that selection to reduce age at first calving, in general, should improve longevity and productivity traits of females, but the increase in body weight at first calving would reduce some of the productivity traits. The genetic correlations of IPP, EPP, PD and P12 with RPPP suggest that selection to reduce age at first calving should improve the productivity trait of the females.